2013
DOI: 10.1186/1471-2474-14-231
|View full text |Cite
|
Sign up to set email alerts
|

Delta III reverse shoulder arthroplasty in the treatment of complex 3- and 4-part fractures of the proximal humerus: 6 to 42 months of follow up

Abstract: BackgroundThere is a growing tendency for complex proximal humerus fractures (PHF) in osteoporotic patients to be treated with reverse shoulder arthroplasty (RSA). It has been proposed that RSA has more benefits than other treatment options. The aim of our study was to investigate preoperative characteristics as well as clinical and radiological outcomes in patients with complex 3- or 4-part PHF who had undergone primary RSA.MethodsPatients with a minimum follow-up of 6 months who had undergone a primary RSA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 25 publications
0
8
0
2
Order By: Relevance
“…Raiss et al demonstrated a reduction in survivorship at 10 and 15 years after TSA performed with cement secondary to pain and implant loosening; revision procedures occurred at a mean of 8.8 years from the date of implantation 125 . The five RSA studies with minimum follow-up of 5 years noted scapular notching and instability as the most common complications 28 [33][34][35][36][37][38][39][44][45][46][47][48]50,51,53,54,[56][57][58][59]61,64,65,67,69,70,73,75,79,81,[88][89][90][91][92][93][94][95][96][97][98][99][100][101][102]104,105,…”
mentioning
confidence: 99%
“…Raiss et al demonstrated a reduction in survivorship at 10 and 15 years after TSA performed with cement secondary to pain and implant loosening; revision procedures occurred at a mean of 8.8 years from the date of implantation 125 . The five RSA studies with minimum follow-up of 5 years noted scapular notching and instability as the most common complications 28 [33][34][35][36][37][38][39][44][45][46][47][48]50,51,53,54,[56][57][58][59]61,64,65,67,69,70,73,75,79,81,[88][89][90][91][92][93][94][95][96][97][98][99][100][101][102]104,105,…”
mentioning
confidence: 99%
“…Klein et al [32] achieved a similar CMS of 68, although the tuberosities were excised in all patients. Mattiassich et al [33] reported a mean CMS of 54.8 (range 18–95) and a mean DASH score of 37.5 (range 2.9–81) in 32 patients with a mean age of 72 years and treated with primary RSA after four-part fractures of the proximal humerus. Also, our result is aligned to staged bilateral RSA not performed in the acute traumatic setting [[34], [35], [36], [37], [38], [39]].…”
Section: Discussionmentioning
confidence: 99%
“…6). Die Vorteile dieser Technik im Vergleich zum Kopferhalt liegen v. a. in der schnellen Reduktion der Schmerzsymptomatik und der geringen Revisionsrate [46,50].…”
Section: Inverse Prothesenunclassified